Resources and tools for the high-throughput, multi-omic study of intestinal microbiota. (27th November 2017) - Blanco-Míguez, Aitor; Fdez-Riverola, Florentino; Sánchez, Borja; Lourenço, Anália
Abstract: The human gut microbiome impacts several aspects of human health and disease, including digestion, drug metabolism and the propensity to develop various inflammatory, autoimmune and metabolic diseases. Many of the molecular processes that play a role in the activity and dynamics of the microbiota go beyond species and genic composition and thus, their understanding requires advanced bioinformatics support. This article aims to provide an up-to-date view of the resources and software tools that are being developed and used in human gut microbiome research, in particular data integration and systems-level analysis efforts. These efforts demonstrate the power of standardized and reproducible computational workflows for integrating and analysing varied omics data and gaining deeper insights into microbe community structure and function as well as host–microbe interactions.